Caffeine Content of Bondowoso Arabica Ground Coffee with Variation of Roasting Profile and Type of Packages - Savitri, Dyah Ayu; Arum, Ayu Puspita; Suud, Hasbi Mubarak; Farisi, Oria Alit; Patricia SM, Susan Barbara; Kusmanadhi, Bambang; Munandar, Denna Eriani (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2022)
Bondowoso Arabica coffee is a type of coffee that grows on the slopes of Mount Ijen-Raung. It has a high commercial value and distinctive taste. Coffee processing applications from roasting, grinding, packaging and brewing to storage will affect the quality of coffee. Caffeine is one of the compounds in coffee that contributes to bitterness and has certain pharmacological effects. This study aimed to determine the caffeine content of Bondowoso Arabica coffee harvested on August 2021 which was obtained from Sukosari Lor village with various roast profiles and types of packaging. In this study, Arabica coffee was roasted with light roast, medium roast and dark roast profiles. Then each treatment was mashed to obtain ground coffee. Ground coffee was put in a standing pouch made of polyethylene terephthalate (PET) with a thickness of 75 microns; polypropylene (PP) with a thickness of 100 microns; and polypropylene (PP) with a thickness of 120 microns and then stored for three months. During the storage of first and third months, caffeine levels were measured. Based on the results of the study, the caffeine content was increase along with higher roasting temperature. During the storage process, the caffeine content in ground coffee packaged using PP decreased the most.